Preventive Effect of M. cochinchinensis on Melanogenesis via Tyrosinase Activity Inhibition and p-PKC Signaling in Melan-A Cell - Juyong Kim (MDPI AG, 2021)
Whitening research is of particular interest in the cosmetics market. The main focus of whitening research is on melanogenesis inhibition through tyrosinase activity. The mechanism of melanogenesis is involved with tyrosinase activity and p-PKC signaling. In this study, we used Momordica cochinchinensis (Lour.) spreng, a tropical fruit found throughout Southeast Asia, to investigate the inhibitory effect of melanogenesis. M. cochinchinensis contains a high concentration of polyphenols, flavonoids, and unsaturated fatty acids, which might be related to antioxidant activity. This study aimed to determine whether M. cochinchinensis extracts inhibit melanin synthesis in melan-A cells by inhibiting tyrosinase activity and p-PKC signaling. M. cochinchinensis was divided into pulp and aril and extracted under various conditions, and it was confirmed that all pulp and aril extracts have high contents of both phenols and flavonoids. Melan-A cells were treated with PMA for three days to induce melanin synthesis. After PMA treatment, M. cochinchinensis extracts were added to cultured media in a dose-dependent manner. Melanin contents and MTS were used to determine the amount of melanin in live cells. M. cochinchinensis extracts were evaluated for their effects on tyrosinase activity and p-PKC signaling pathways by Western blotting. It was found that M. cochinchinensis extract treatment decreased the amount of melanin and suppressed p-PKC expression. Additionally, tyrosinase activity was reduced after M. cochinchinensis extract treatment in a dose-dependent manner. Therefore, it was concluded that M. cochinchinensis could be used in antimelanogenesis and functional cosmetic materials to improve whitening.